Diacerein attenuates sepsis shock mortality through combined suppression of vascular inflammation, stiffness, and permeability - Luo, Minghao; Jiang, Yi; Peng, Yuce; Lv, Dingyi; He, An; Huang, Longxiang; Xia, Yong; Luo, Suxin; Li, Yuanjing (Phytomedicine (Stuttgart), 2025)
Sepsis shock mortality remains critically high due to dysregulated vascular inflammation and permeability. Diacerein (DIA), an anthraquinone derivative with anti-inflammatory properties, shows promise, but its vascular protective mechanisms in sepsis are unclear. This study investigated DIA's effects on sepsis shock mortality and its underlying vascular mechanisms, aiming to elucidate its novel multi-mechanistic actions compared to existing therapeutic approaches. Cecal ligation and puncture (CLP)-induced septic mice received low-dose or high-dose DIA. Survival, hemodynamics, organ injury markers (lactate, ALT, AST, creatinine, BUN), and serum cytokines were assessed. Bulk RNA sequencing (RNA-seq) was performed on mesenteric microvessels and aortas. Vascular reactivity, permeability (Evans Blue), endothelial junction proteins (ZO-1, VE-cadherin), extracellular matrix (ECM) components (COL1A1, COL3A1), and screened-out genes (NF-κB p65, STATs) were analyzed. Endothelial cell-specific STAT2 knockdown (EC-STAT2 KD) mice were generated using AAV9. DIA significantly improved 72 h survival, attenuated hypotension, organ injury, and systemic inflammation. Mesenteric RNA-seq revealed that DIA suppressed inflammatory pathways and CXC chemokines. Aortic RNA-seq identified inhibition of collagen synthesis genes, confirmed by reduced protein levels and improved vascular tension. Transcriptomic and functional analyses further uncovered a previously unreported role for DIA in selectively inhibiting STAT2 activation within the vasculature. DIA selectively inhibited STAT2 function (mRNA, protein, and Tyr690 phosphorylation) in vasculature, but not in the spleen. EC-STAT2 KD reduced vascular leakage, restored barrier proteins, and improved survival. Combining DIA with EC-STAT2 KD offered no additional survival benefit. Diacerein attenuates sepsis shock mortality by concurrently suppressing vascular inflammation via NF-κB and chemokines, improving macrovascular reactivity/ECM remodeling, and reducing microvascular leakage by selectively inhibiting endothelial STAT2 activation. This is the first study to comprehensively demonstrate the efficacy of Diacerein in septic shock through a multi-mechanism vascular strategy and to identify its novel inhibitory effect on the STAT2 pathway in the endothelium.